2019
DOI: 10.1097/iae.0000000000002187
|View full text |Cite
|
Sign up to set email alerts
|

Focal Disruptions in Ellipsoid Zone and Interdigitation Zone on Spectral-Domain Optical Coherence Tomography in Pachychoroid Pigment Epitheliopathy

Abstract: Focal disruptions of the EZ/IZ band can develop in pachychoroid eyes in the absence of subretinal fluid, with a stable clinical course, and possibly as a result of regression of drusenoid lesions. This may represent an atrophic form of pachychoroid manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Vision-threatening atrophy or geographic atrophy rarely develops. 27 This study has several limitations. Measurements were performed manually, and at times borders of each layer or points of measurement, particularly under the pachydrusen were difficult to determine.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vision-threatening atrophy or geographic atrophy rarely develops. 27 This study has several limitations. Measurements were performed manually, and at times borders of each layer or points of measurement, particularly under the pachydrusen were difficult to determine.…”
Section: Discussionmentioning
confidence: 92%
“…Pachydrusen are frequently present as a singular lesion having small extent and distribution of lesion area, and frequently located outside the fovea. Vision‐threatening atrophy or geographic atrophy rarely develops …”
Section: Discussionmentioning
confidence: 99%
“…25,35,51 A small-scale hospital-based study reported that focal RPE atrophy and overlying outer retinal layer changes may be observed after the regression of pachydrusen, but vision-threatening atrophy or GA rarely develops. 52 Taken together, pachydrusen does not seem to affect RPE directly and may have little pathological significance on macular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…A definitive cut-off point of CT to define CSCR as one of the pachychoroid spectrum disorders is not determined yet. Enhanced Depth Imagine (EDI) OCT significantly shows increased CT in the macula compared to the peripapillary region [22][23][24][25]. Found that the mean subfoveal CT was 450±66µm (range=356-595µm) in eyes with CSCR and 367±86µm (range=220-554µm) in the unaffected fellow eye.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…OCT can be used to identify prognostic biomarkers like intra-retinal hyper-reflective dots, which usually progress from inner to outer retinal layers and correlate with poor visual prognosis. In addition, it can measure the central retinal thickness (CRT), choroidal thickness (CT), and choroidal vascularity index (CVI) [22][23][24][25].…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%